2022
DOI: 10.3390/antibiotics11121797
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bioactive Compounds from Streptomyces actinomycinicus PJ85 and Their In Vitro Antimicrobial Activities against Methicillin-Resistant Staphylococcus aureus

Abstract: Antibiotic-resistant strains are a global health-threatening problem. Drug-resistant microbes have compromised the control of infectious diseases. Therefore, the search for a novel class of antibiotic drugs is necessary. Streptomycetes have been described as the richest source of bioactive compounds, including antibiotics. This study was aimed to characterize the antibacterial compounds of Streptomyces sp. PJ85 isolated from dry dipterocarp forest soil in Northeast Thailand. The 16S rRNA gene sequence and phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…We found that the extract showed antibacterial activity against Staphylococcus aureus and Escherichia coli, and the diameter of the bacteriostatic zone is about 14 mm. Amin et al [20] screened a Streptomyces from the desert of Egypt and characterized its antibacterial activity with multidrug-resistant S.aureus. and the diameter of the bacteriostatic zone was in 4 mm-22 mm.…”
Section: Chemical Structure Of the Pigmentmentioning
confidence: 99%
“…We found that the extract showed antibacterial activity against Staphylococcus aureus and Escherichia coli, and the diameter of the bacteriostatic zone is about 14 mm. Amin et al [20] screened a Streptomyces from the desert of Egypt and characterized its antibacterial activity with multidrug-resistant S.aureus. and the diameter of the bacteriostatic zone was in 4 mm-22 mm.…”
Section: Chemical Structure Of the Pigmentmentioning
confidence: 99%
“…Many Streptomyces species have been reported to produce secondary metabolites that exhibit antibacterial and herbicidal activity. For example, Streptomyces actinomycinicus PJ85 exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus by producing actinomycin D and dihomo-γ-linolenic acid [6]. Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%